Прийняття інноваційних маркетингових рішень на підприємствах харчової промисловості - Бергер, Аліна Дмитрівна (My University, 2023)
Для підвищення конкурентоспроможності, активності інноваційного розвитку, збільшення ефективності діяльності підприємств харчової промисловості на підприємствах виникає потреба у прийнятті зважених і економічно обґрунтованих інноваційних маркетингових рішень. Харчова наука активно розвиває напрямки маркетингового комплексу, а саме: Product ‒ базується на випуску продуктів спеціального призначення: дієтичного лікувального/профілактичного харчування, харчування для спортсменів дітей, людей похилого віку, вагітних жінок тощо; Price ‒ враховується моніторинг цін у торговельних мережах, аналіз сучасної ринкової кон’юнктури, цін на аналогічну і нову продукцію конкурентів; Place ‒ усунення зайвих ланцюгів (посередників) за рахунок виробництва продукції під власною торговою на замовлення великих роздрібних мереж; Promotion ‒ включає тренд-сеттінг, WOM-технологію, buzz-маркетинг, event-маркетинг, product placement, life-placement, провокаційний маркетинг, entertainment маркетинг, флешмоб, тизер тв інші. Представлено розподіл на традиційні та інноваційні підходи у системі маркетингу підприємства, що призводить до появи нових видів маркетингу (латеральний, віртуальний, партизанський, вірусний, нейромаркетинг тощо). Наведені приклади застосування даних видів маркетингу у відомих брендах для впровадження на підприємствах харчової промисловості. Applications of innovative marketing theory testify that all types of innovations the influence and improve the constituents of marketing complex of the enterprise. Classic concepts of “marketing” and “innovations” indissolubly connected and co-operate with each other. There is a requirement in the acceptance of self-proved and economically reasonable innovative marketing decisions of the enterprise, that assist the increase of competitiveness, providing of innovative development, increase of economic efficiency, activity effectiveness of the enterprises. It is the vital problem for the enterprises of food industry that actively carry on innovative activity, searching and realization of administrative decisions that provide competitive edges at high-competition market of food products. Food science actively develops different directions of marketing complex, namely: commodity politics (Product) ‒ is based on producing of products of the special setting: dietary curative/prophylactic food, food for sports children, elderly people, pregnant women and others like that; pricing (Price) is taken into account monitoring of prices in trade networks, analysis of modern market conditions and prices on the analogical and new products of competitors; channels of sale (Place), elimination of unnecessary chains (mediators) due to the production of goods under the own trade on the order of large retail networks; communication politics (Promotion) includes trend-setting, WOM- technology, buzz-marketing, event-marketing, product placement, life - placement, provocative marketing, entertainment marketing, flash mob, teaser and other. Distribution on traditional and innovative approaches in the system of marketing enterprises that result to introduction of new types of marketing (lateral, virtual, partisan, client-oriented, viral, neuromarketing and others like that) is presented. Examples of application of these types of marketing are made in the well-known brands of companies that assisted to the increase of incomes, and for the ground of expediency of their introduction and development on the enterprises of food industry.
Keywords: кафедра маркетингу; інновації (маркетинг); innovation (marketing); маркетингові рішення; 12Р; система маркетингу; інноваційна діяльність підприємства; marketing solutions